2021
DOI: 10.1111/aogs.14151
|View full text |Cite
|
Sign up to set email alerts
|

A systematic overview of the spermatotoxic and genotoxic effects of methotrexate, ganciclovir and mycophenolate mofetil

Abstract: Introduction Immunosuppressant drugs are increasingly being used in the reproductive years. Theoretically, such medications could affect fetal health either through changes in the sperm DNA or through fetal exposure caused by a presence in the seminal fluid. This systematic overview summarizes existing literature on the spermatotoxic and genotoxic potentials of methotrexate (MTX), a drug widely used to treat rheumatic and dermatologic diseases, and mycophenolate mofetil (MMF), which alone or supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…These reduced levels of testosterone are also likely the cause of the strong alteration in sexual behavior seen in Tg+GCV males. Several studies have reported that prenatal or adult exposure to GCV can be spermatotoxic and induce drastic effects on testes ( 56 , 57 ) even if a recent systematic overview indicates a limited number of studies investigating the effect of GCV and could not conclude on the spermatotoxic effects of this substance ( 58 ). In all cases, effects of GCV on testes and germ lines were found when high doses were administered subcutaneously (100 – 300 mg/kg) ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…These reduced levels of testosterone are also likely the cause of the strong alteration in sexual behavior seen in Tg+GCV males. Several studies have reported that prenatal or adult exposure to GCV can be spermatotoxic and induce drastic effects on testes ( 56 , 57 ) even if a recent systematic overview indicates a limited number of studies investigating the effect of GCV and could not conclude on the spermatotoxic effects of this substance ( 58 ). In all cases, effects of GCV on testes and germ lines were found when high doses were administered subcutaneously (100 – 300 mg/kg) ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medication with antioxidants can improve semen quality through reducing OS [ 35 ]. However, several medications have been reported to have a negative impact on spermiogenesis, such as antidepressants, antibiotics, and antihypertensive agents [ 36 ]. Increased scrotal temperature due to fever or varicocele can cause a temporary decrease in sperm quality, where OS may play a role [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 For example, sulfasalazine and methotrexate are effective first-line conventional synthetic disease-modifying antirheumatic drugs (csDMARDs), but have been linked to adverse events, including gastrointestinal complications, infections, skin reactions, neurotoxicity, malignancies, infertility, and negative effects on sperm that may or may not be reversible. [3][4][5][6][7] Treatment selection is especially challenging among advanced therapies. While the American College of Rheumatology and EULAR align on recommendations for first-line therapies, approximately one-third of patients have an inadequate response to conventional csDMARDs, such as methotrexate and sulfasalazine, and often progress to one of multiple available advanced treatments.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%